Comparison of Physical Performance Profiles in Freestyle and Greco-Romen Wrestlers - Gokhan Deliceoğlu; Erkan Tortu; Selman Kaya (Physical Education of Students, 2022)
Background and Study Aim. This study aimed to examine the differences between a range of performance parameters in -Greco-Roman and Freestyle wrestlers. The study group consisted of 60 young wrestlers, of which 30 were Greco-Roman, and 30 were freestyle.